Influence of exercise training mode on arterial diameter: A systematic review and meta-analysis. Issue 1 (January 2016) - Black, Jane M.; Stöhr, Eric J.; Shave, Rob; Esformes, Joseph I.
Abstract: Objectives: To examine whether differences in arterial diameter exist between athletes participating in endurance, resistance or mixed exercise training. Design: A systematic review with meta-analysis. Methods: Random effects meta-analyses of the weighted mean difference in aortic, carotid, brachial and femoral arterial diameters, height and body mass were conducted on data from 16 peer-reviewed studies indexed on PubMed, MEDLINE, SCOPUS and Sport Discus. Effect sizes were calculated as the standardised difference in means ( δ ), and used to compare endurance ( n  = 163), resistance ( n  = 192), and mixed trained athletes ( n  = 360), with controls ( n  = 440). Results: Compared to controls, endurance athletes displayed the greatest difference in diameter in the brachial artery ( δ  = 1.84, 95% CI: 0.59, 3.09, p  < 0.01), whereas for mixed athletes, the greatest difference in diameter occurred in the femoral artery ( δ  = 3.65, 95% CI: 2.21, 5.10, p  < 0.01), despite there being no differences in height or body mass between these groups. Resistance athletes had a significantly greater body mass ( p  = 0.047) and aortic diameter ( δ  = 1.81, 95% CI: 1.58, 2.05, p  < 0.01) than controls, however differences in other vessels could not be determined through meta-analysis due to insufficient data. Conclusions: Our results provide evidence for localised arterial differences, which occur more extensively in peripheral vessels (brachial and femoral). Chronically, vascular remodelling may occur as a result of the specific haemodynamic conditions within each vessel, which likely differs depending on the mode of exercise. In the future, empirical research is needed to understand the effect of resistance training on chronic vascular remodelling, as this is not well documented.